Active Community-Based Case Finding of Endemic Leishmaniasis in West Bengal, India - Subhasish Kamal Guha; Ashif Ali Sardar; Amartya Kumar Misra; Pabitra Saha; Anwesha Samanta; Dipankar Maji; Amitabha Mandal; Punita Saha; Supriya Halder; Kabiul Akhter Ali; Sibajyoti Karmakar; Dipendra Sharma; et al. (Springer, 2024)
Abstract Introduction The ongoing visceral leishmaniasis (VL) elimination programme in India is targeting the elimination of the disease VL but not the pathogen. The persistence of hidden parasite pool may initiate a resurgence in suitable conditions. This study dealt with a novel approach to unearth such pathogen pool and their proper management to prevent the resurgence of VL. Materials and Methods We deployed a new approach for detection of pathogen pool by following up the VL and post kala-azar dermal leishmaniasis patients treated during the last 10 years along with mass sero-surveillance within a radius of 500 m of recently treated individuals. Results We followed up 72.6% (3026/4168) previously treated VL and post kala-azar dermal leishmaniasis patients and diagnosed 42 (1.4%) new and 38 (1.3%) recurrent post kala-azar dermal leishmaniasis. We detected 93 asymptomatic leishmanial infection, 8 VL and 1 post kala-azar dermal leishmaniasis by mass sero-surveillance. Conclusion Our three-step process including mapping and follow-up of previously treated cases, mass surveillance within 500 m of radius of known cases, and 6 monthly follow-on clinical and serological screening of asymptomatic cases, enabled detection of previously undetected cases of post kala-azar dermal leishmaniasis and VL. Recurrent post kala-azar dermal leishmaniasis deserves special attention regarding their treatment guideline. Early diagnosis and effective treatment of all leishmaniasis cases will hasten pathogen elimination and prevent resurgence of VL. This may help the policymakers to develop appropriate strategy for elimination of pathogen to prevent resurgence of VL.